1999
DOI: 10.1177/0011000099275001
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Impairment

Abstract: This article reviews the professional literature on the topic of evaluating the competence of trainees in professional psychology training programs including program policies, procedures, and actual practice for identifying, remediating, and, in extreme cases, dismissing trainees who are judged unable to provide competent, professional care. This review covers the literature on the following major issues related to trainee performance: (a) problems with definitions of impairment, (b) established professional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 97 publications
0
57
0
Order By: Relevance
“…Only a small proportion of supervisees in health service psychology programs demonstrate significant problems in professional competence, but most academic and intern ship programs report at least one supervisee with compe tence problems in the previous five years (Forrest et al, 1999). When this occurs it can be helpful to consider the multiple contexts in which problem behavior is embedded (e.g., cultural beliefs, licensure and accreditation, peers, faculty, supervisors; Forrest et al, 2008).…”
Section: O M a I N F: P R O F E S S I O N A L C O M P E T E N C E Pmentioning
confidence: 99%
“…Only a small proportion of supervisees in health service psychology programs demonstrate significant problems in professional competence, but most academic and intern ship programs report at least one supervisee with compe tence problems in the previous five years (Forrest et al, 1999). When this occurs it can be helpful to consider the multiple contexts in which problem behavior is embedded (e.g., cultural beliefs, licensure and accreditation, peers, faculty, supervisors; Forrest et al, 2008).…”
Section: O M a I N F: P R O F E S S I O N A L C O M P E T E N C E Pmentioning
confidence: 99%
“…Such dilemmas may occur internally, among colleagues, or both and include the potential for both under-and overidentifying TPPC Forrest et al, 1999;Forrest, Elman, & Shen-Miller, 2008;Kaslow et al, 2007). For example, faculty afraid of appearing biased may under-identify students from traditionally oppressed backgrounds as having competence problems, and faculty of color may believe that their colleagues will not validate, support, or act on their concerns about a majority student and thus avoid identifying students as having competence problems (Cook, 1994;Norton & Coleman, 2003).…”
mentioning
confidence: 99%
“…Procedure E-mails were sent to Faculty Sponsors of NASP-approved School Psychology graduate programs and to other faculty through the Trainers of School Psychologists Listserv. The faculty were asked to forward via email the information about the study to the NASP Student Representative(s), and the forwarded message included a survey link that was provided by SurveyMonkey.com (Finley, 2010). The survey included an informed consent page, which indicated that taking the survey was voluntary and participants could back out at any time.…”
Section: Participantsmentioning
confidence: 99%
“…The research on student impairment that does exist is characterized by confusing terminology and poor methodology (Brear, Dorian, & Luscri, 2008;Forrest, Elman, Gizara, & Vacha-Haase, 1999). In particular, terms such as distressed, impaired, or problematic student have been used interchangeably in the literature (Vacha-Haase et al, 2004), along with the catch-all term unsuitability (e.g., Brear et al, 2008), with no provision of a unified definition.…”
mentioning
confidence: 99%